Mechanochemical Synthesis of Expanded Vermiculite with Urea for Filler into Alginate/Collagen Spherical Capsules: A Urea Slow-release System - de Oliveira, Douglas Santos; Jaerger, Silvia; Marangoni, Rafael (Orbital: The Electronic Journal of Chemistry, 2021)
The annual growth of the world population increasingly provokes the search for highly productive agriculture, with an effective and economical application of fertilizers capable of supplying the necessary nutrients to the plants. In this context, the development of technologies to control these fertilizers in the environment is relevant. This study presents a potential slow-release fertilizer created from the intercalation of urea in the expanded vermiculite (EV) and encapsulated in a sphere constituted of alginate/collagen. The intercalation tests were performed by the mechanochemical process between EV and urea, and the intercalated materials were characterized by XRD, TGA/DSC, and FTIR. The results showed that urea was intercalated at all studied ratios, but the sample containing 20% of urea (EVU20%) did not present peaks from the starting reagents. Thus, the sample EVU20% was chosen for the encapsulation process and release test. Urea concentration released was determined by colorimetric analysis, and the test revealed that the spheres produced with EVU20% encapsulated into an alginate/collagen matrix were able to release the urea up to 210 hours. Therefore, this system has the potential to be a new fertilizer of slow-release to be applied in agriculture, promoting the gradual release of urea for plant development. DOI: http://dx.doi.org/10.17807/orbital.v13i2.1488